Effect of Ultrasonic Energy on Reductive Cleaning of Dyed Polyester Fabrics - (:unkn) unknown (ASIAN JOURNAL OF CHEMISTRY, 2012)
After dyeing of polyester with disperse dyes, reductive cleaning processes were applied by using sodium ditionite, sodium hydroxide and thiourea dioxide. In this study effects of ultrasonic and conventional methods on reductive cleaning processes were investigated in terms of Delta E*, Delta L*, Delta a*, Delta b*, *Delta C* and Delta H* colour values, K/S values and fastness properties. After conventional (70 degrees C, 20 min) and ultrasonic (70 degrees C, 10 min) reductive cleaning processes, values were compared and total colour differences for ultrasonic process for all reductive cleaning agents were in acceptable range. K/S values were higher for ultrasonic sodium ditionite and sodium hydroxide reductive cleaning processes depending on the sodium hydroxide concentration. K/S values were generally higher for conventional thiourea dioxide and sodium hydroxide reductive cleaning processes. It was obtained that ultrasonic energy process does not have a negative effect on fastness properties of the samples.
Keywords: Disperse dyed polyester fabric; Reductive cleaning; Ultrasonic method; Conventional method; COTTON